The impact of authentic materials (news articles, essays, podcasts) on reading motivation and reading comprehension in 9th-grade EFL students - Teshaboyeva, Shakhnoza Ziyodulla kizi; Shamsutdinova, Lyutsiya Rafailovna (The Lingua Spectrum, 2026)
This article examines the role of authentic materials in teaching reading to ninth-grade students in English as a Foreign Language (EFL) classrooms. Authentic materials, such as newspapers, magazines, online articles, advertisements, and short stories created for real-life communication, are believed to make language learning more meaningful and engaging for learners. The study focuses on how these materials influence students’ reading motivation, comprehension abilities, and overall interest in reading activities. Through classroom observations, reading tasks, and learner feedback, the research evaluates whether authentic texts encourage students to participate more actively in lessons and develop better reading strategies. The findings suggest that exposure to real-world language increases learners’ confidence, enriches vocabulary acquisition, and improves their ability to understand contextual meaning. In addition, authentic materials help create a more interactive and learner-centered environment, promoting critical thinking and communication skills. The article concludes that integrating authentic resources into reading instruction can significantly support both language development and long-term reading engagement among ninth-grade EFL students.